2021
DOI: 10.3390/biology11010013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Biochemical Parameters during Antiviral Treatment in COVID-19 Patients

Abstract: (1) Background: The antiviral treatment for COVID-19 disease started to be largely used in 2020 and has been found to be efficient, although it is not specific for SARS-CoV-2 virus. There were some concerns that it may produce liver damage or other side effects. (2) Methods: The aim of this study was to observe if antiviral therapy is affecting liver parameters or producing other side-effects in patients hospitalized for COVID-19 disease. The study included a group of patients hospitalized in the internal medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The liver function parameter was evaluated before, during, and after admission, as well as before, during, and after discharge. In this trial, 36 patients were treated with Lopinavir/Ritonavir, 85 patients with Remdesivir, and 151 patients with FVP [ 34 ]. Patients with critical previous liver harm (persistent hepatitis with hepatocytes or severe cholestasis, liver cirrhosis, and liver metastases) were excluded from the study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver function parameter was evaluated before, during, and after admission, as well as before, during, and after discharge. In this trial, 36 patients were treated with Lopinavir/Ritonavir, 85 patients with Remdesivir, and 151 patients with FVP [ 34 ]. Patients with critical previous liver harm (persistent hepatitis with hepatocytes or severe cholestasis, liver cirrhosis, and liver metastases) were excluded from the study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral treatment was proposed to an approximately equivalent number of females (139 patients) and males (133 patients), and the age of the patients enrolled in the research was between 26 and 88 years, with an average age of 60.18 years [ 33 ]. FVP treatment for COVID-19 patients revealed an increase in the level of hepato-renal markers [ 34 ]. The present study found that the most frequent chronic diseases in the patients in this study were DM (19.6%), HTN (13.0%), and both DM and HTN (13.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, all COVID-19 patients should be tested regularly for these biochemical parameters, and re-testing is recommended in severe patients after discharge until liver function levels return to normal. Furthermore, uric acid values should also be monitored with favipiravir, and extra attention should be paid to neutrophils and platelets with remdesivir and lopinavir/ritonavir ( Marc et al, 2021 ). A liver biopsy is recommended for patients with one of the following three conditions:(a) Persistent elevation of hepatic biochemical parameters or signs of deterioration in liver function after discontinuation of the suspected drug; (b) cases of DILI where continued use or re-exposure to the implicated agent is contemplated; (c) liver biochemistry abnormalities persist beyond 180 d, especially if associated with symptoms (e.g., itching) or signs (e.g., jaundice and hepatomegaly) ( Chalasani et al, 2021 ).…”
Section: Clinical Managementmentioning
confidence: 99%
“…However, it has also opened many doors to the new development of novel technologies, such as telemedicine. In this context, the editors of the journal Biology decided at the very beginning of this worldwide dilemma to create a Special Issue, entitled “Coronavirus Disease 2019 (COVID-19).” This Special Issue encompasses thirty-one articles covering various aspects of the current pandemic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. With contributions from esteemed scientists from across the globe, this Special Issue sheds light on various aspects of the pandemic, including, but not limited to, epidemiology, pathophysiology, risk factors, and possible treatment options.…”
mentioning
confidence: 99%